Estrutura Molecular e Supramolecular de Pirazolo[1,5- a]pirimidinas - Frizzo, Clarissa Piccinin (2010)
This work describes the molecular and supramolecular structure of fourteen pyrazolo[1,5-a]pyrimidines from bond lengths, torsion angles, angles between planes and interatomic distances. The data discussed were originated from xray and theoretical calculations. Torsion angle N1-N8-C3a-N4, algles between planes of pyrazole and pyrimidine rings and the pyrazolo[1,5-a]pyrimidine RMS value showed that the fused rings are plane. The heterocyclic ring bond lengths demonstrated that the p-electrons are delocalized by resonance and the peripheral electronic distribution of this p-electrons is similar to the naphthalene. The bond length obtained from theoretical calculations (AM1, PM3, RM1 e ab initio) have a correlation with experimental for pyrazolo[1,5-a]pyrimidine ring bonds and for bonds of their substituents.The supramolecular assembly of pyrazolo[1,5-a]pyrimidine reveals that interactions type halogen···Lewis base (Cl···N, F···F, Cl···Cl, Cl···Br), halogen···p (F···p, Cl···p e Br···p) and p-p interactions (pyrazole, pyrimidine and aryl) were the main interactions observed by self-assembly of the pyrazolo[1,5-a]pyrimidines. The atoms in supramolecular synthons were invariable with modifications of substituent at C5. However, was sensitive to variations of substituents at C3. This composes a notable example of substituent effect in the synthon robustness. The halogenated functions at C7(CCl3, CF3), C3 (Br) and in remote positions at C5 (4-Br-Ph) present the competition between chlorine and bromine atoms in the formation of supramolecular synthons. These observations are in accordance with recent s-hole theory and are some of few experimental example of theory. Finally, the aromaticity of pyrazolo[1,5-a]pyrimidines was determined by geometric index HOMA (Harmonic Oscillator Model of Aromaticity) from theoretical (AM1, PM3, RM1 e ab initio) and x-ray bond length. In this work, was also proposing new parameters to heterocyclic HOMA calculations. The results show HOMA values higher than 0.900 that is in accordance with aromaticity properties of these systems.